(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The project of a full-fledged atmospheric aesthetics is largely committed to the descriptive tools of felt experiences, just in keeping with a phenomenological – or, better, a neo-phenomenological – approach. However, description, what we might call ‘atmospherography’, all the more one allegedly accomplished from a first-person point of view, is always a partial, if not particular, perspective. Thus a coherent aesthetics of atmospheres has also to envisage a systematic way of connecting the manifold of descriptions in a theory, call it ‘atmospherology’, which in turn should be able to account for a number of possible experiential counterfactuals. The present paper critically explores the consistency of both the epistemological and ontological consequences of an aesthetics of atmospheres, as sketched mainly by Gernot Böhme, a pioneer and a leading figure in this research field, and tries to specify at least some refutability conditions for such a theory.